INCIDENCE OF CELIAC DISEASE AMONG CHILDREN DIAGNOSED WITH TYPE I DIABETES - Muhammad Burhan Anjum; Basil Siddique; Tayiba Ilyas; Faheem Ashraf; Qanita Shahzad; Muhammad Faizan Ul Haq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Celiac disease (CD) is an autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals, and it frequently coexists with Type 1 Diabetes Mellitus (T1DM), another autoimmune condition. Objectives: This study aimed to determine the prevalence of celiac disease (CD) among children with Type 1 Diabetes Mellitus (T1DM) and to evaluate the clinical and histological characteristics of CD in this population Study design: Cross sectional study Settings: This study was conducted at Akhtar Saeed Trust Hospital Lahore from November 2023 to May 2024. Study duration: 6th October 2020 to 5th April 2021 Methods: We conducted a cross-sectional study involving 125 pediatric patients with T1DM, aged 5 to 18 years, at a tertiary care hospital. We screened participants for CD using serological tests for tissue transglutaminase IgA (tTG-IgA), deamidated gliadin peptide IgG (DGP-IgG) in case of selective IgA deficiency, and confirmed positive cases with upper gastrointestinal endoscopy and small bowel biopsy. We recorded demographic data and clinical symptoms.. Results: Out of 125 patients, 18 (14.4%) tested positive for CD-specific antibodies. Among these, 12% were positive for tTG-IgA, and 2.4% with IgA deficiency were positive for DGP-IgG. Histological examination revealed that 50% of seropositive patients had Marsh III (villous atrophy), 22.2% had Marsh II (hyperplastic lesions), and 16.7% had Marsh I (infiltrative lesions). Notably, 38.9% of patients with CD were asymptomatic, with abdominal pain (27.8%) and diarrhea (22.2%) being the most common symptoms Conclusion: Prevalence of CD among children with T1DM in our study (14.4%) supports the higher risk of CD in this population. The significant proportion of asymptomatic cases highlights the importance of routine CD screening in T1DM patients to prevent potential complications and ensure optimal management. Early diagnosis and multidisciplinary care are essential to address both conditions effectively.